Activation of coagulation and inhibition of fibrinolysis in the lung after inhalation of lipopolysaccharide by healthy volunteers - Maris, Nico A.; de Vos, Alex F.; Bresser, Paul; van der Zee, Jaring S.; Meijers, Joost C.; Lijnen, Roger H.; Levi, Marcel; Jansen, Henk M.; van der Poll, Tom (Thrombosis and Haemostasis, 2005)
Pneumonia is frequently associated with changes in coagulation and fibrinolysis in the bronchoalveolar space. To determine the effect of lipopolysaccharide (LPS) on the hemostatic balance in the human lung, six healthy subjects inhaled nebulized LPS or saline in a randomized cross-over study and bronchoalveolar lavage fluid was obtained six hours thereafter. LPS induced soluble tissue factor and thrombin-antithrombin complexes and inhibited plasminogen activator activity in BALF. Additionally plasminogen activator inhibitor type 1 production was upregulated after LPS inhalation. LPS also elicited local activation of neutrophils (release of elastase, myeloperoxidase and bactericidal/permeability increasing protein) and secretion of interleukin (IL)-6 and IL-8. Inhalation of LPS by healthy humans reproduces major features of the procoagulant response to inflammatory and infectious lung diseases and may be used as a novel model to evaluate pathogenetic mechanisms and new interventions.
Keywords: Lipopolysaccharide; lung; coagulation; fibrinolysis; human